Răspuns :
1+(2 (3+5×-20)÷6)×7=8
1+(2 (-17+5×)÷6)×7=8
1+2 (-17+5×)supra6×7=8
1+-17+5×supra3×7=8
1+7 (-17+5×)supra3)=8
1+-119+35×supra3=8
3-119+35×=24
-116+35×=24
35×=24+116
35×=140
×=4
1+(2 (-17+5×)÷6)×7=8
1+2 (-17+5×)supra6×7=8
1+-17+5×supra3×7=8
1+7 (-17+5×)supra3)=8
1+-119+35×supra3=8
3-119+35×=24
-116+35×=24
35×=24+116
35×=140
×=4
1 + { 2 × [ 3 + ( x - 4 ) × 5 ] : 6 } × 7 = 8
{ 2 × [ 3 + ( x - 4 ) × 5 ] : 6 } × 7 = 8 - 1
2 × [ 3 + ( x - 4 ) × 5 ] : 6 = 7 : 7
2 × [ 3 + ( x - 4 ) × 5 ] = 1 × 6
3 + ( x - 4 ) × 5 = 6 : 2
3 + ( x - 4 ) × 5 = 3
( x - 4 ) × 5 = 3 - 3
x - 4 = 0 : 5
x - 4 = 0
x = 0 + 4
x = 4